Continuous Renal Replacement Therapy in Pediatric Patients With Acute Kidney Injury After Liver Transplantation - Sun, Yan; Gao, Sinan; Wang, Xingqiang; Yu, Lixin; Xu, Min; Gao, Wei; Sun, Chao; Wang, Bing (Frontiers in Pediatrics, 2022)
Objective This study aimed to explore the clinical application of continuous renal replacement therapy (CRRT) in pediatric patients with acute kidney injury (AKI) after liver transplantation. Methods Pediatric patients with liver transplantation performed were retrospectively investigated. Those who developed AKI within one year after surgery were divided into CRRT and non-CRRT groups. The preoperative/intraoperative conditions and postoperative complications of the two groups were compared along with the prognoses of the groups to analyze the high-risk factors for and the conditions of CRRT. Results 189 (36.91%) patients developed AKI within one year after surgery. There were 18 patients in the CRRT group and 171 in the non-CRRT group. The differences in the preoperative conditions were not statistically significant between the two groups. Compared with the non-CRRT group, the CRRT group had significantly longer transplantation times, higher volumes of intraoperative hemorrhage, and increased incidence of postoperative unscheduled surgery, postoperative primary nonfunction of the transplanted liver, secondary liver transplantation, hepatic artery occlusion, and intestinal fistula (P < 0.05). The mean time to initiate CRRT was 28 days after surgery, the median number of CRRT treatments per patient was 3.3 , the average duration of each treatment was 10.1 hours, and the average rate of the decrease in blood creatinine per treatment was 25.6% . There were statistically significant differences in the one- and two-year survival rates (P < 0.001) between the CRRT and non-CRRT groups. Conclusion The incidence of AKI after liver transplantation in pediatric patients was high, and CRRT effectively improved multi-organ functional impairment in those patients.